Beam-wave interaction analysis of a 42 GHz, 200 kW CW gyrotron - Ashutosh; Singh R.; Jain P.K. (My University, 2025)
In this paper, the self-consistent large-signal formulation is used to study the beam-wave interaction mechanism in a gyrotron oscillator. The nonlinear interaction has been computed by solving the set of self-consistent nonlinear equations along the interaction length using numerical method. Consequently, the computation of energy, phase, output power, and efficiency of a gyrotron is made. The computed results were found to be matching with the published results. A 42 GHz, 200 kW output power gyrotron operating in TE 03 mode is analysed using this analysis and results found meeting desired specifications. © 2011 IEEE.